THE IMPLEMENTATION OF PROJECT-BASED LEARNING TO DIRECT STUDENTS IN WRITING A RESEARCH PROPOSAL - Wahyuni, Sri (Language Circle: Journal of Language and Literature, 2014)
This paper aims to describe the implementation of Project-Based Learning (PBL) Method in Linguistic and Educational Research classroom. PBL is defined as âa systematic teaching method that engages students in learning knowledge and skills through an extended inquiry process structured around complex, authentic questions and carefully designed products and tasksâ, Markham, Larmer, and Ravitz (2003:4). The problem investigated is how the implementation of Project-Based Learning directs students in writing research proposal. The subjects were 30 students of the sixth semester of the English Department, Semarang State University, 2012-2013 academic year. The subject course provides students with knowledge of the aims, principles, and kinds of linguistic and educational research methods and designs and the skill and practice in constructing research proposals. Besides, the research class enriches studentsâ understanding about research as a scientific inquiry to solve problems through some stages such as identifying and formulating problem, gathering and analyzing data, and ways to publish the research results (Saleh, 2012). Therefore, equiping students with skills and experiences in writing research proposal is significantly important.